2009
DOI: 10.1037/a0014373
|View full text |Cite
|
Sign up to set email alerts
|

Juggling multiple racial identities: Malleable racial identification and psychological well-being.

Abstract: The authors examined the link between malleable racial identification and psychological well-being among self-identified multiracial adults. Malleable racial identification refers to the tendency to identify with different racial identities across different social contexts. Results across three studies suggested that malleable racial identification was associated with lower psychological well-being. Study 2 found that unstable regard (i.e., fluctuating private regard about their multiracial background) was the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(89 citation statements)
references
References 48 publications
3
85
1
Order By: Relevance
“…Further, multiracial individuals also appear to face some additional psychological burdens relating to how they are perceived by themselves and others. For example, multiracial individuals are sometimes judged more negatively than their monoracial counterparts (Sanchez & Bonam, 2009), and multiracial individuals are sometimes called upon to define or defend their racial identity in ways that monoracial individuals are not, a process that can come with psychological costs (Sanchez, Shih, & Garcia, 2009;Townsend et al, 2009). It appears that identifying with more than one racial category is associated with more positive well-being in adolescents (Binning, Unzueta, Huo, & Molina, 2009), suggesting that an overemphasis on discrete racial categories may have negative consequences for at least some multiracial individuals, for whom having their identity accurately recognized can be important.…”
Section: The Experiences Of Multiracial Individualsmentioning
confidence: 99%
“…Further, multiracial individuals also appear to face some additional psychological burdens relating to how they are perceived by themselves and others. For example, multiracial individuals are sometimes judged more negatively than their monoracial counterparts (Sanchez & Bonam, 2009), and multiracial individuals are sometimes called upon to define or defend their racial identity in ways that monoracial individuals are not, a process that can come with psychological costs (Sanchez, Shih, & Garcia, 2009;Townsend et al, 2009). It appears that identifying with more than one racial category is associated with more positive well-being in adolescents (Binning, Unzueta, Huo, & Molina, 2009), suggesting that an overemphasis on discrete racial categories may have negative consequences for at least some multiracial individuals, for whom having their identity accurately recognized can be important.…”
Section: The Experiences Of Multiracial Individualsmentioning
confidence: 99%
“…As noted earlier, a fixed or rigid racial identity may be pathological or stagnant as one's internal positions should demonstrate flexibility (Blackman, 2005;Parham, 1989). Conversely, although many racial identity theories present a dynamic identity as an optimal outcome, Sanchez et al (2009) found malleable racial identity was associated with decreased psychological health and wellbeing in multiracial individuals. Research should be completed to more clearly understand to what extent and how a dynamic identity is healthy and should be internally or externally controlled, and to what extent and in what types of situations a fixed racial identity is a sign of strength versus being maladaptive or a possible indication of psychopathology.…”
Section: Discussionmentioning
confidence: 96%
“…An attractor-based model also supports multistabilities and multiple simultaneous crises (Nowak et al, 2005). Individuals can display concurrent attraction to multiple racial categories or experience multiple racial crises (Chao & Moon, 2005;Helms, 1995;Oyserman, 2008;Poston, 1990;Renn, 2000Renn, , 2003Root, 1990Root, , 1996Sanchez, Shih, & Garcia, 2009). This multiplicity extends to feedback.…”
Section: Reframing Existing Theories and Constructs Of Race And Raciamentioning
confidence: 99%
“…Third, malleable identities can be adaptive or maladaptive (Sanchez et al, 2009). Sussman's (2000) model of cultural identity and its inherent notion of dynamic identity may be useful for further work on ethnic identity dynamics and well-being .…”
Section: Trajectory 1: Towards Greater Interconnectedness Between Ethmentioning
confidence: 99%